Arsitektur dan Seni Candi Kedulan - Dwi Pradnyawan (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
The Kedulan Temple, which was completely restored in 2019, showed many new things to be observed, moreover the discovery of three inscriptions on the inner courtyard of the temple made it even more interesting to study. This paper will discuss the architectural and artistic aspects of the Kedulan Temple and its relation to the inscriptions found with the aim of looking at the characteristics of architecture and art and their relation to the periodization of the Kedulan Temple. The research method used is descriptive analysis with an emphasis on comparative analysis of architectural forms and decorative arts. The studies that have been carried out showed that the Kedulan Temple is a model of a Hindu-Shiva temple with distinctive architectural characteristics and has decorative motifs that are in harmony with the year number of the inscription, namely in the second half of the 9th century AD (869 AD). Specifically, the decorative motifs of the Kedulan Temple prove that this temple is one of the youngest or belongs to the final phase of the Central Javanese art. Keywords: candi; architecture; decorative arts; inscriptions